Selected Collective Bargaining Agreements of Washington Two-Year Colleges - National Education Association, Washington, DC.; National Education Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Seventeen collective bargaining agreements between the boards of trustees and faculty associations of selected community colleges in Washington are presented, representing contracts in effect in 1987. The following colleges are represented: Peninsula College, Olympic College, Skagit Valley College, Everett Community College, Shoreline Community College, Bellevue Community College, Highline Community College, Green River Community College, Pierce College, Centralia College/South Puget Sound Community College, Wenatchee Valley College, Yakima Valley Community College, Spokane Community College/Spokane Falls Community College, Columbia Basin College, Walla Walla Community College, Whatcom Community College, Tacoma Community College, and Edmonds Community College. With some variation among agreements, the following topics are covered: board recognition; association/federation rights; personnel or employee rights, relations, and benefits; general working conditions; compensation; part-time faculty; faculty evaluation; academic freedom; grievance procedures; leaves; tenure; dismissal; reduction-in-force; calendar and workload; salary placement and advancement; college governance; prior practices; uninterrupted education activities; scope of agreement; and duration. Some agreements include articles on home study, travel reimbursements, summer quarter teaching, community service and support programs, grants and contracts, and special projects. Salary schedules are included for all of the agreements. (MDB)
ERIC Note: 1,050p.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Collective Bargaining; College Faculty; Community Colleges; Contracts; Department Heads; Employment Practices; Faculty Promotion; Faculty Workload; Fringe Benefits; Grievance Procedures; Job Layoff; Leaves of Absence; Personnel Policy; Released Time; Teacher Dismissal; Teacher Retirement; Teacher Salaries; Tenure; Two Year Colleges; Unions; NEA Contracts -- Washington; National Education Association; Legal/Legislative/Regulatory Materials